Purely cortical anaplastic ependymoma - Romero, Flávio Ramalho [UNESP]; Zanini, Marco Antônio [UNESP]; Ducati, Luis Gustavo [UNESP]; Vital, Roberto Bezerra [UNESP]; Lima Neto, Newton Moreira de [UNESP]; Gabarra, Roberto Colichio [UNESP] (Hindawi Publishing Corporation, 2012)
Ependymomas are glial tumors derived from ependymal cells lining the ventricles and the central canal of the spinal cord. It may occur outside the ventricular structures, representing the extraventicular form, or without any relationship of ventricular system, called ectopic ependymona. Less than fifteen cases of ectopic ependymomas were reported and less than five were anaplastic. We report a rare case of pure cortical ectopic anaplastic ependymoma.